Diffuse involvement of the leptomeninges by tumour–a clinical and pathological study of 63 cases. Issue 653 (March 1980) - Boyle, R.; Thomas, M.; Adams, J. H.
Abstract : The clinical and pathological features of 63 cases of post-mortem-proved diffuse infiltration of the leptomeninges by tumour are presented. A wide variety of tumours of the nervous system, both primary and secondary, was found to give rise to such involvement, with adenocarcinoma having a particular propensity to behave in this manner. Dysfunction of cranial and spinal nerves, a confusional state and headache were prominent clinical features. Examination of the cerebro-spinal fluid was found to be less useful diagnostically in cases of primary tumours of the nervous system with leptomeningeal involvement than in cases of diffuse infiltration of the meninges by carcinoma.